Flame Badges and Virtual Pets: Gamified Sociality on Douyin - Hui Lin; Rafal Zaborowski (Social Media + Society)
This article examines Douyin’s gamified features to investigate whether and how they facilitate online sociality. Drawing on literature on online sociality and gamification, this study demonstrates how Douyin’s gaming elements introduce a playful dimension to social interactions and examines the implications of transforming sociality into a game. Using a mixed-method approach comprising the walkthrough method and diary-interview technique, the study finds that gamified features—such as friendship badges, quantified levels, and virtual pets—can encourage social behavior and strengthen interpersonal bonds. However, these effects are primarily confined to small, strong-tie friendship groups and do not extend to larger, weak-tie networks. The findings suggest that Douyin users often display heightened awareness of how algorithms exploit their social behaviors, prompting them to adopt cautious and critical digital practices. The article makes both empirical and methodological contributions by offering a case study of gamification in socialization and demonstrating the utility of the diary-interview approach for analyzing user interactions.